Firefighter Hand Anthropometry and Structural Glove Sizing: A New Perspective. (December 2015) - Hsiao, Hongwei; Whitestone, Jennifer; Kau, Tsui-Ying; Hildreth, Brooke
Objective: We evaluated the current use and fit of structural firefighting gloves and developed an improved sizing scheme that better accommodates the U.S. firefighter population. Background: Among surveys, 24% to 30% of men and 31% to 62% of women reported experiencing problems with the fit or bulkiness of their structural firefighting gloves. Method: An age-, race/ethnicity-, and gender-stratified sample of 863 male and 88 female firefighters across the United States participated in the study. Fourteen hand dimensions relevant to glove design were measured. A cluster analysis of the hand dimensions was performed to explore options for an improved sizing scheme. Results: The current national standard structural firefighting glove-sizing scheme underrepresents firefighter hand size range and shape variation. In addition, mismatch between existing sizing specifications and hand characteristics, such as hand dimensions, user selection of glove size, and the existing glove sizing specifications, is significant. An improved glove-sizing plan based on clusters of overall hand size and hand/finger breadth-to-length contrast has been developed. Conclusion: This study presents the most up-to-date firefighter hand anthropometry and a new perspective on glove accommodation. The new seven-size system contains narrower variations (standard deviations) for almost all dimensions for each glove size than the current sizing practices. Application: The proposed science-based sizing plan for structural firefighting gloves provides a step-forward perspective (i.e., including two women hand model–based sizes and two wide-palm sizes for men) for glove manufacturers to advance firefighter hand protection.